The role of negroes in the ethnic formation of Ceará: The need of a reappraisal - Chandler, Billy Jaynes (Revista de Ciências Sociais, 2020)
The ethnic formation of Ceará has received considerable discussion in scholarly works dealing with that area, particularly with respect to the role of the indigenous peoples, the Indians.